Determination of the samples required of water-sensitive paper in experiments related spray technology - Alexandre Ballarotti Nascimento (Semina: Ciências Agrárias, 2013)
The raise in the numbers of samples increase the confidence level of the results. However little is know about the minimum number of water-sensitive papers cards that must be used in studies of spray technology. Thus, the aim of this paper was to determine the minimum number of water-sensitive papers cards used in spray experiments, based on the variables: percentage of coverage, number of drops per cm2 and volume median diameter (VMD). It were realized an experiment in factorial design 2x2 with five replicates, each containing 36 cards. With the objective to have variability among the treatments, the factors involveed were nozzles (TR110-01 and ULD120-015) and operational pressures (138 and 276 kPa), because the size of droplets is modified even by the nozzle as by operational pressures. As estimative precision, the mean errors assumed was 20%, 15% and 10%, that generated numbers of samples as: 7, 12 and 26, respectively, for percentage of coverage; 5, 8 and 16, respectively, for number of drops per cm2; and 1.2 and 4 respectively, for volume median diameter (VMD). Analysis of variance complemented by Tukey test at 5% probability were realized for the average of 36 cards and the average of the minimum number of papers (samples) determined. Comparing statically the averages obtained in the experiment for each variable for n=36 samples and n= samples determined at 20% error, noted that the results are identical in both situations, demonstrating that spray rates and different droplet sizes influenced directly in the parameters evaluated. It is possible to conclude that the minimum number of water-sensitive papers cards per repetition (1 m2 for this experiment) is 7,5, and 1 for percentage of coverage, number of droplet per cm2 and volume median diameter (VMD), respectively.